2021
DOI: 10.1186/s12981-021-00389-1
|View full text |Cite
|
Sign up to set email alerts
|

Early ART-initiation and longer ART duration reduces HIV-1 proviral DNA levels in children from the CHER trial

Abstract: Background Reduction of the reservoir of latent HIV-infected cells might increase the possibility of long-term remission in individuals living with HIV. We investigated factors associated with HIV-1 proviral DNA levels in children receiving different antiretroviral therapy (ART) strategies in the children with HIV early antiretroviral therapy (CHER) trial. Methods Infants with HIV  <  12 weeks old with CD4%  ≥  25% were randomized in the CHER tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…As expected, no association was observed between HIV reservoir and the time to any ART, including monotherapy in early years (p=0.443 for tDNA and ρ =-0.079; p=0.8567 for uDNA). These findings suggest that shades of delay in ART initiation in this cohort associate with tDNA levels and are in line with previous reports in PHIV ( 50 , 51 ). Interestingly, however, there was no relationship between uDNA levels and time to ART, suggesting that factors other than ART influence presence/absence of uDNA.…”
Section: Resultssupporting
confidence: 93%
“…As expected, no association was observed between HIV reservoir and the time to any ART, including monotherapy in early years (p=0.443 for tDNA and ρ =-0.079; p=0.8567 for uDNA). These findings suggest that shades of delay in ART initiation in this cohort associate with tDNA levels and are in line with previous reports in PHIV ( 50 , 51 ). Interestingly, however, there was no relationship between uDNA levels and time to ART, suggesting that factors other than ART influence presence/absence of uDNA.…”
Section: Resultssupporting
confidence: 93%
“…These results are in agreement with the findings of other studies in Africa. 34,35 Statistically significant improvements in weight gain over the 24-month research period and at each six-month follow-up visit since ART was initiated was observed. Although the focus was on changes in WAZ, there was consistent improvement in both WAZ and L/HAZ, with more rapid increases in weight as opposed to gradual increases in length or height.…”
Section: Discussionmentioning
confidence: 96%
“…The possible justification might be being on ART for a longer duration may expose individuals to better HIV‐related knowledge, 52 which may further improve their adherence level 53 and could result in a good viral suppression rate. A similar study indicated longer ART duration is key to HIV‐ DNA reduction 54 . Whereas, a study conducted in Mekelle showed that the duration of ART was not significantly related to SLART failure 41 .…”
Section: Discussionmentioning
confidence: 95%
“…A similar study indicated longer ART duration is key to HIV-DNA reduction. 54 Whereas, a study conducted in Mekelle showed that the duration of ART was not significantly related to SLART failure. 41 Against the result of this study, evidence from South Africa showed that as the duration of ART increases the likelihood of TF increases.…”
Section: Discussionmentioning
confidence: 97%